Ureteric Stones less than 1.5 Cm: Comparison of Laser Vs. Pneumatic Lithotripsy: A Single Center Study - Muhammad Asif, Junaid Jamil Khattak, Zakir Khan, Kausar Anwar, Romana Bibi, Shahzad-ur-Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ureterorenoscopy (URS) and intracorporeal lithotripsy (ICL) is the first-choice treatment for ureteric stones less than 1.5 cm. Various options forintracorporeal lithotripsy exist such as pneumatic, Laser and Ultrasonic. Aim: To assess the safety and efficacy of laser versus pneumatic lithotripsy in treating ureteric stones of less than 1.5cm via Ureterorenoscopy. Methods: A total of 182 patients who underwent URS and intracorporeal in the department of UROLOGY LRH to were reviewed retrospectively from December 2021-December 2022 after ethical approval. Two groups were made on the basis of type oflithotripsy used (112 patients in the pneumatic lithotripsy (PL) group and 70 patients in the Laser lithotripsy (LL) group. Stone-free rate (SFR), mean operation time (MOT), mean hospital stay (MHS), and complications rate were evaluated for both groups. Results: Mean age of LL Patients was 41.1±3.9 years and PL patients 38.2±4.5 years. 68.4% of the study participants were males. LL had more upper ureter stones 17 (24.4%). LL's drawbacks outweighed its benefits in treating proximal ureteral calculi. Table 2 outlines postoperative complications and efficacy. Comparing the complications more PL patients had ureteric perforations (4.4%), postoperative fever (2.9%) and mucosal injury (5.7%) with p-value ≥0.05%. Mean operation time and hospital stay were less in LL patients, an immediate stone-free rate more (93.3%) in LL patients while stone migration more in PL patients 20(28.6%) with a statistically significant (p-value ≤0.05). Practical implication: Patients with renal stones will easily be treated with laser and pneumatic with less complications rate and short hospital stay than open surgery. Conclusion: For the treatment of ureteral stones, the PL and LL methods were effective and safe. However, it's possible that the LL class' SFR was higher.. Keywords: Ureteric Stones, Laser Lithotripsy, Pneumatic Lithotripsy, Comparison